History and Theories of Psychology / A Critical Perspective - Elcock Jonathan; Jones Dai (Hodder Arnold, 2001)
This book introduces the core issues of critical psychology from a historical perspective. Preface, Introduction, History as Metatheory, The Founding of Psychology, The Early Development of Psychology, The Development of Applied Psychology, Psychoanalysis and Psychology, Psychology and Society, The Development of Social Psychology, The Rise of Cognitivism, Psychology and ''Minorities'', The Nature and Role of Contemporary Psychology, Everyday Psychology, Methodological Issues, Cognitive Psychology, Cognitive Psychology, Connectionism, Social Constructionism, Conclusions, Appendix: Useful Resources, References, Index.